Chapter One Hundred Years of Daily Sea-Surface Temperature from the Hopkins Marine Station in Pacific Grove, California - Breaker, Laurence C. (Taylor & Francis, 2023)
The 100-year record of daily sea-surface temperature (SST) acquired at the Hopkins Marine Station (HMS) in Pacific Grove, California, is one of the longest oceanographic records in existence. It is exceeded in length by the record at Scripps Pier by only 3 years. The history of the record at HMS, the methods used to gather the data, the problems that were encountered, and finally, the scientific significance of this record are presented. Reconstructing a complete version of the 100-year time series record was not straightforward. Two major gaps had to be filled using data from another site, and variation in the time of day for sample collection was addressed to better standardise the SST values presented. The observations were first examined for their oceanographic content based on the relevant timescales involved that ranged from daily to the record length, i.e., centennial. The major sources of variability included the El Niño phenomenon, the Pacific Decadal Oscillation, and the Marine Heat Wave (MHW) that began in 2014. The impact of the MHW cannot be overstated, and it was well represented in the data from the HMS. The use of the historical temperature record for studies of long-term changes in species and communities in the biological literature is highlighted. Finally, a set of conclusions is presented highlighting the important contributions of the SST dataset that are only possible through dedicated long-term environmental monitoring programmes such as the one reported here.